PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA KONSEP MAGNET KELAS V SDN BRUMBUNGAN LOR - Megawati; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is oriented towards improving the in-depth reasoning skills of fifth grade students of SD Negeri Brumbungan Lor in the learning process of magnet concept. The main issue encountered is the lack of active involvement of students in teaching and learning activities. Students tend to be passive, only receiving information without processing or criticizing it, even reluctant to answer questions from the teacher. This is exacerbated by the use of boring learning methods and patterns that are not very appealing. To overcome these problems, a Classroom Action Research (PTK) approach is used which consists of four stages, namely planning, action implementation, observation, and reflection. The learning model applied was Project Based Learning (PjBL), which encourages students to be more active, creative, and directly involved in the learning process. The results showed a significant increase in students' critical thinking skills. Based on the observation sheet, critical thinking skills increased from 39.34 in round 1 session 1, changed to 50 in session 2, and again rose to 70.26 to reach 80.52 in round 2.The increase was also seen in learning outcomes, with an average initial test score of 62.10 (47.36%), increased to 68.15 (68.42%) in round 1, and transformed to 81.05 (94.73%) in round 2.Thus, it can be concluded that the application of the Project Based Learning model proved effective in improving critical thinking skills.